Novel Göttingen Miniswine Model of Heart Failure With Preserved Ejection Fraction Integrating Multiple Comorbidities - Sharp, Thomas E. (JACC Basic Transl Sci, 2021)
A lack of preclinical large animal models of heart failure with preserved ejection fraction (HFpEF) that recapitulate this comorbid-laden syndrome has led to the inability to tease out mechanistic insights and to test novel therapeutic strategies. This study developed a large animal model that integrated multiple comorbid determinants of HFpEF in a miniswine breed that exhibited sensitivity to obesity, metabolic syndrome, and vascular disease with overt clinical signs of heart failure. The combination of a Western diet and 11-deoxycorticosterone acetate salt−induced hypertension in the Göttingen miniswine led to the development of a novel large animal model of HFpEF that exhibited multiorgan involvement and a full spectrum of comorbidities associated with human HFpEF.